LANGUAGE MIXING AND SWITCHING IN MALAYALAM - ENGLISH BILINGUAL APHASICS - Shyamala Chengappa, Krupa Elizabeth Daniel, Sapna Bhat
Language mixing defined as inappropriate switching from one language to another, is a frequently observed recovery pattern among bilingual aphasics. In spite of the fact that a significant amount of population in India is bilingual, language mixing is one of the least researched areas. Also, the distinction between language mixing exhibited by bilingual aphasics and the normal process of code switching employed by neurologically normal bilingual speakers is not very marked. Hence, the present study was taken up with the purpose of investigating the similarities and differences in the code switchingbehaviors of aphasics and neurologically normal Malayalam-English bilingual speakers. There was an increase in code switching behavior but the quality of switches did not differ when compared with those in normal subjects. These results could be a reflection of increased reliance on two languages as a compensatory strategy in this set of subjects